Low-Complexity Erasure Decoding of Staircase Codes - Clelland, William Stewart (Université d'Ottawa / University of Ottawa, 2023)
This thesis presents a new low complexity erasure decoder for staircase codes in optical interconnects between data centers. We developed a parallel software simulation environment to measure the performance of the erasure decoding techniques at output error rates relevant to an optical link. Low complexity erasure decoding demonstrated a 0.06dB increase in coding gain when compared to bounded distance decoding at an output error rate of 3 × 10⁻¹². Further, a log-linear extrapolation predicts a gain of 0.09dB at 10⁻¹⁵. This performance improvement is achieved without an increase in the maximum number of decoding iteration and keeping power constant. In addition, we found the optimal position within the decoding window to apply erasure decoding to minimize iteration count and output error rates, as well as the erasure threshold that minimizes the iteration count subject to the constrained erasure decoding structure.
Keywords: Forward Error Correction; Erasure; Staircase Codes; Low Complexity